A method of testing the homogeneity of an aluminum matrix composite powder
Patent Information
- Application Number
- CN202611142391.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-13
AI Technical Summary
粉末混合不均会导致SiC颗粒团聚或偏析,烧结/致密化后易形成孔洞、疏松、界面脱粘等缺陷,直接破坏微观组织完整性
本发明的检验方法简单易操作,可高效检验铝基复合材料粉末(即混合粉末)均匀性并为改善铝基复合材料粉末混合均匀性提供技术支持。
Smart Images

Figure CN122901026A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum-based composite materials technology, and in particular to a method for testing the uniformity of aluminum-based composite powder. Background Technology
[0002] Aluminum-based silicon carbide composites, as high-performance metal matrix composites, emerged in the late 1970s and became a global research hotspot in the materials field from the 1980s onwards. After decades of development, they have moved from the laboratory to large-scale industrial applications, becoming one of the key materials supporting high-end manufacturing. In its early stages, the focus was on exploring preparation processes, with technologies such as powder metallurgy, stir casting, and melt infiltration gradually maturing. In recent years, with breakthroughs in technologies such as additive manufacturing and in-situ synthesis, the material properties and preparation efficiency have continued to improve, and the application boundaries have been continuously expanded.
[0003] This material cleverly combines the advantages of an aluminum matrix and a silicon carbide (SiC) reinforcing phase, resulting in outstanding core advantages. It boasts low density, high specific strength and modulus, significant lightweighting effect, and strong load-bearing capacity, far superior to pure aluminum and ordinary aluminum alloys. It also exhibits high thermal conductivity, a low and adjustable coefficient of thermal expansion, excellent heat dissipation performance, and can suppress thermal stress failure by adjusting the SiC content to match the coefficient of thermal expansion of materials such as chips and ceramics. Furthermore, it possesses wear resistance, high temperature resistance, good dimensional stability, and damping vibration reduction properties, enabling it to maintain stable performance over long periods under harsh operating conditions.
[0004] Leveraging these advantages, aluminum-based silicon carbide composite materials have been widely applied in several key fields. In the aerospace industry, they are used in satellite structural components, aircraft heat dissipation components, and engine assemblies to achieve weight reduction, efficiency improvement, and stable thermal control. In the electronic packaging field, they have become a core material for IGBT substrates, 5G base station heat dissipation housings, and laser packaging bases, resolving the contradiction between miniaturization and high heat dissipation requirements. In the new energy vehicle field, they are used in motor controllers and braking system components, balancing lightweighting and reliability. Furthermore, they are gradually replacing traditional materials in precision machine tools, rail transportation, and optical instruments, demonstrating broad application prospects.
[0005] In the preparation of aluminum-based silicon carbide composite materials, powder uniformity inspection is a core prerequisite and indispensable for ensuring material quality. Uneven powder mixing can lead to SiC particle agglomeration or segregation, resulting in defects such as pores, looseness, and interfacial debonding after sintering / densification, directly compromising the integrity of the microstructure. Simultaneously, uneven distribution causes fluctuations in the material's mechanical properties (strength, hardness) and thermophysical properties (thermal conductivity, coefficient of thermal expansion), producing significant anisotropy and failing to meet the consistency requirements of high-end components. Furthermore, hard particles formed by SiC agglomeration exacerbate tool wear, reduce machining accuracy and yield, and easily become stress concentration sources, inducing crack initiation and significantly shortening the service life of components. Therefore, rigorously inspecting powder uniformity is crucial for stabilizing material properties, reducing failure risks, ensuring batch repeatability and industrial mass production stability, and has significant practical implications for improving the reliability and application value of composite materials. Summary of the Invention
[0006] The purpose of this invention is to provide a method for testing the uniformity of aluminum-based composite powder, so as to solve the problems existing in the prior art, realize efficient testing of the uniformity of aluminum-based composite powder (i.e., mixed powder), and provide technical support for improving the mixing uniformity of aluminum-based composite powder.
[0007] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of the present invention: a method for testing the uniformity of aluminum-based composite material powder, comprising the following steps: S1: Samples were taken from four different locations in the aluminum-based composite powder, and the sample volumes of the four samples were the same. S2: Weigh the four samples taken and calculate the relative standard deviation of the weight; S3: Perform particle size analysis and color observation on the four samples taken, and record the results. 90 And calculate the relative standard deviation of particle size (i.e., D). 90 (relative standard deviation); S4: Uniformity determination: If the relative standard deviation of the weight of the four samples exceeds 5%, step S3 is not required, and the aluminum-based composite powder is directly determined to be non-uniform; if the relative standard deviation of the weight of the four samples is within 5%, step S3 is performed; if the relative standard deviation of the particle size of the four samples is within 2.5% and the color is uniform, the aluminum-based composite powder is determined to be uniform (i.e., if the relative standard deviation of the particle size of the four samples is not within 2.5% or the color is non-uniform, the aluminum-based composite powder is determined to be non-uniform).
[0008] Furthermore, the four different locations are specifically the four different locations of east, west, south, and north.
[0009] Furthermore, the sampling is specifically performed using a sampler with a fixed volume.
[0010] Furthermore, the sampling volume (i.e., the volume of the sampler) is 1 cm³. 3 .
[0011] Furthermore, the particle size detection and color observation are performed using a stereomicroscope.
[0012] Furthermore, when observing color, the brightness of the stereomicroscope is 70-100.
[0013] Furthermore, the uniform color specifically refers to the uniform color of all four samples.
[0014] Furthermore, the aluminum-based composite powder is composed of aluminum matrix powder and reinforcing particles.
[0015] Furthermore, the reinforcing particles are SiC (silicon carbide) particles.
[0016] Optionally, the particle size of the reinforcing particles is 10-60 μm.
[0017] Optionally, the particle size of the aluminum matrix powder is <150 μm.
[0018] Optionally, the mass fraction of reinforcing particles in the aluminum-based composite powder is 15-75%.
[0019] Optionally, the mixing speed is 200-400 rpm and the time is 4-8 h.
[0020] The present invention discloses the following technical effects: The testing method of the present invention is simple and easy to operate, and can efficiently test the uniformity of aluminum-based composite powder (i.e., mixed powder) and provide technical support for improving the mixing uniformity of aluminum-based composite powder.
[0021] This invention constructs a progressive powder uniformity detection system from macroscopic to microscopic levels. First, the overall macroscopic uniformity of the powder is initially assessed using weight indicators. After confirming that the macroscopic state is satisfactory, a refined analysis of particle size and color indicators is conducted on the microscopic region, and standardized acceptance thresholds are set for each indicator. This layered, progressive inspection logic can quickly eliminate substandard powders, effectively shortening the detection cycle and improving detection efficiency. Simultaneously, relying on a multi-dimensional, layer-by-layer verification mode from macroscopic to microscopic levels, it achieves comprehensive and in-depth analysis of powder uniformity, significantly improving detection accuracy and analytical depth, and reducing the risk of misjudgment of powder quality. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 The results of stereomicroscopic color observation of the sample taken in Example 1 are shown.
[0024] Figure 2 The results of stereomicroscopic color observation of the sample taken in Example 2 are shown.
[0025] Figure 3 The results of stereomicroscopic color observation of the sample taken in Example 3 are shown.
[0026] Figure 4 The results of stereomicroscopic color observation of the sample taken in Example 4 are shown.
[0027] Figure 5 The results of stereomicroscopic color observation of the sample taken in Example 5 are shown.
[0028] Figure 6 The results of stereomicroscopic color observation of the sample taken in Comparative Example 3 are shown. Detailed Implementation
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0031] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0032] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0033] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0034] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0035] Unless otherwise specified, room temperature or normal temperature refers to 20-30°C in the following embodiments and comparative examples of the present invention.
[0036] All raw materials used in the following embodiments and comparative examples of this invention are commercially available products. Unless otherwise specified, the particle size of SiC particles is 10-60 μm; unless otherwise specified, the aluminum matrix powder is 6061 aluminum-based alloy powder, and unless otherwise specified, the particle size of the aluminum matrix powder is <150 μm.
[0037] Example 1 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 15% and the total weight of the mixed powder is 10 kg.
[0038] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 200 rpm and the mixing time is 4 h.
[0039] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0040] Step S4: Weigh the four samples and record the weights as 1.67g, 1.69g, 1.72g, and 1.65g, respectively, and calculate the relative standard deviation as 2.99%.
[0041] Step S5: Use a stereomicroscope to perform particle size detection and color observation on the sample (adjust the brightness within the range of 70-100 according to the field of view, observe the contrast and color of the mixed powder sample), and record D. 90The micrometers were 112.32 μm, 112.85 μm, 113.42 μm, and 112.78 μm, respectively, with a calculated relative standard deviation of 0.39%. Color observation results showed that all four samples were uniformly blue-green (the stereomicroscopic color observation result of one sample is shown below). Figure 1 As shown, the color observation results of the other three samples under stereomicroscopy are consistent with it, that is, the colors of the four samples are consistent.
[0042] Step S6: Based on steps S4 and S5, the relative standard deviation of the weights of the four samples is within 5%, D 90 If the relative standard deviation is within 2.5% and the color of the stereomicroscope image is uniform, the mixed powder is considered to be uniformly mixed.
[0043] Example 2 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 30% and the total weight of the mixed powder is 20kg.
[0044] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 250 rpm and the mixing time is 5 h.
[0045] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0046] Step S4: Weigh the four samples and record the weights as 1.75g, 1.78g, 1.80g, and 1.83g, respectively, and calculate the relative standard deviation as 3.37%.
[0047] Step S5: Use a stereomicroscope to perform particle size detection and color observation on the sample (adjust the brightness within the range of 70-100 according to the field of view, observe the contrast and color of the mixed powder sample), and record D. 90 The micrometers were 102.35 μm, 103.45 μm, 102.85 μm, and 104.85 μm, respectively, with a calculated relative standard deviation of 1.04%. Color observation results showed that all four samples were uniformly blue-green (the stereomicroscopic color observation result of one sample is shown below). Figure 2 As shown, the color observation results of the other three samples under stereomicroscopy are consistent with it, that is, the colors of the four samples are consistent.
[0048] Step S6: Based on steps S4 and S5, the relative standard deviation of the weights of the four samples is within 5%, D 90 If the relative standard deviation is within 2.5% and the color of the stereomicroscope image is uniform, the mixed powder is considered to be uniformly mixed.
[0049] Example 3 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 45% and the total weight of the mixed powder is 30 kg.
[0050] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 300 rpm and the mixing time is 6 h.
[0051] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0052] Step S4: Weigh the four samples and record the weights as 1.88g, 1.90g, 1.94g, and 1.92g, respectively, and calculate the relative standard deviation as 2.58%.
[0053] Step S5: Use a stereomicroscope to perform particle size detection and color observation on the sample (adjust the brightness within the range of 70-100 according to the field of view, observe the contrast and color of the mixed powder sample), and record D. 90 The micrometers were 90.85 μm, 90.12 μm, 89.56 μm, and 91.23 μm, respectively, with a calculated relative standard deviation of 0.82%. Color observation results showed that all four samples were uniformly blue-green, and their colors were consistent (the stereomicroscopic color observation result of one sample is shown below). Figure 3 (As shown).
[0054] Step S6: Based on steps S4 and S5, the relative standard deviation of the weights of the four samples is within 5%, D 90 If the relative standard deviation is within 2.5% and the color of the stereomicroscope image is uniform, the mixed powder is considered to be uniformly mixed.
[0055] Example 4 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 60% and the total weight of the mixed powder is 40 kg.
[0056] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 350 rpm and the mixing time is 7 h.
[0057] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0058] Step S4: Weigh the four samples and record the weights as 2.15g, 2.18g, 2.08g, and 2.12g, respectively. Calculate the relative standard deviation as 4.27%.
[0059] Step S5: Use a stereomicroscope to perform particle size detection and color observation on the sample (adjust the brightness within the range of 70-100 according to the field of view, observe the contrast and color of the mixed powder sample), and record D. 90 The micrometers were 101.23 μm, 100.35 μm, 101.89 μm, and 102.35 μm, respectively, with a calculated relative standard deviation of 0.85%. Color observation results showed that all four samples were uniformly blue-green (the stereomicroscopic color observation result of one sample is shown below). Figure 4 As shown, the color observation results of the other three samples under stereomicroscopy are consistent with it, that is, the colors of the four samples are consistent.
[0060] Step S6: Based on steps S4 and S5, the relative standard deviation of the weights of the four samples is within 5%, D 90 If the relative standard deviation is within 2.5% and the color of the stereomicroscope image is uniform, the mixed powder is considered to be uniformly mixed.
[0061] Example 5 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 75% and the total weight of the mixed powder is 50 kg.
[0062] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 400 rpm and the mixing time is 8 h.
[0063] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0064] Step S4: Weigh the four samples and record the weights as 2.29g, 2.31g, 2.25g, and 2.27g, respectively, and calculate the relative standard deviation as 2.58%.
[0065] Step S5: Use a stereomicroscope to perform particle size detection and color observation on the sample (adjust the brightness within the range of 70-100 according to the field of view, observe the contrast and color of the mixed powder sample), and record D. 90 The micrometers were 96.56 μm, 95.87 μm, 96.45 μm, and 97.86 μm, respectively, with a calculated relative standard deviation of 0.86%. Color observation results showed that all four samples were uniformly blue-green (the stereomicroscopic color observation result of one sample is shown below). Figure 5 As shown, the color observation results of the other three samples under stereomicroscopy are consistent with it, that is, the colors of the four samples are consistent.
[0066] Step S6: Based on steps S4 and S5, the relative standard deviation of the weights of the four samples is within 5%, D 90 If the relative standard deviation is within 2.5% and the color of the stereomicroscope image is uniform, the mixed powder is considered to be uniformly mixed.
[0067] Comparative Example 1 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 55% and the total weight of the mixed powder is 10 kg.
[0068] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 200 rpm and the mixing time is 4 h.
[0069] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0070] Step S4: Weigh the four samples and record the weights as 2.05g, 1.98g, 2.23g, and 1.95g, respectively, and calculate the relative standard deviation as 12.55%.
[0071] Step S5: According to step S4, if the relative standard deviation of the weight of the four samples exceeds 5%, it is directly determined that the mixed powder is not uniform.
[0072] Comparative Example 2 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 30% and the total weight of the mixed powder is 10 kg.
[0073] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 250 rpm and the mixing time is 5 h.
[0074] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0075] Step S4: Weigh the four samples and record the weights as 1.63g, 1.74g, 1.68g, and 1.72g, respectively, and calculate the relative standard deviation as 4.86%.
[0076] Step S5: Use a stereomicroscope to perform particle size detection and color observation on the sample (adjust the brightness within the range of 70-100 according to the field of view, observe the contrast and color of the mixed powder sample), and record D. 90 The corresponding values are 89.2 μm, 96.78 μm, 100.15 μm, and 90.46 μm, respectively, with a calculated relative standard deviation of 5.44%.
[0077] Step S6: Based on steps S4 and S5, the relative standard deviation of the weights of the four samples is within 5%, D 90 If the relative standard deviation exceeds 2.5%, the powder mixture is considered unevenly mixed.
[0078] Comparative Example 3 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 45% and the total weight of the mixed powder is 30 kg.
[0079] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 200 rpm and the mixing time is 6 h.
[0080] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0081] Step S4: Weigh the four samples and record the weights as 1.86g, 1.91g, 1.89g, and 1.94g, respectively. Calculate the relative standard deviation as 3.37%.
[0082] Step S5: Use a stereomicroscope to perform particle size detection and color observation on the sample (adjust the brightness within the range of 70-100 according to the field of view, observe the contrast and color of the mixed powder sample), and record D. 90 The micrometers were 105.74 μm, 106.38 μm, 103.22 μm, and 105.15 μm, respectively, with a calculated relative standard deviation of 1.30%. Color observation results showed that the colors of the four samples were not uniform (the stereomicroscopic color observation result of one sample is shown below). Figure 6 (As shown).
[0083] Step S6: Based on steps S4 and S5, the relative standard deviation of the weights of the four samples is within 5%, D 90 The relative standard deviation is within 2.5%, but the color of the stereomicroscope image is uneven, indicating that the mixed powder is not mixed evenly.
[0084] Comparative Example 4 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 60% and the total weight of the mixed powder is 40 kg.
[0085] Step S2: Weigh the SiC particles and aluminum matrix powder according to the determined total weight of the mixed powder and the mass fraction of the reinforcing particles SiC, and mix them to obtain the mixed powder (i.e., aluminum matrix composite powder). The mixing speed is 350 rpm and the mixing time is 3 h.
[0086] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0087] Step S4: Weigh the four samples and record the weights as 2.03g, 2.19g, 2.37g, and 1.85g, respectively. Calculate the relative standard deviation as 22.21%.
[0088] Step S5: According to step S4, if the relative standard deviation of the weight of the four samples exceeds 5%, it is directly determined that the mixed powder is not uniform.
[0089] Comparative Example 5 A method for testing the uniformity of aluminum-based composite powder, comprising the following steps: Step S1: Determine that the mass fraction of the reinforcing particles SiC is 75% and the total weight of the mixed powder is 50 kg.
[0090] Step S2: Weigh SiC particles and aluminum matrix powder (particle size < 75 μm) according to the determined total weight of the mixed powder and the mass fraction of SiC reinforcing particles, and mix them to obtain mixed powder (i.e. aluminum matrix composite powder). The mixing speed is 400 rpm and the mixing time is 8 h.
[0091] Step S3: Use a fixed volume (V=1cm³) respectively 3 The sampler (a cube with an inner cavity size of 1cm×1cm×1cm) took samples from four different locations in the east, west, south, and north of the mixed powder.
[0092] Step S4: Weigh the four samples and record the weights as 2.31g, 2.35g, 2.29g, and 2.33g, respectively. Calculate the relative standard deviation as 2.58%.
[0093] Step S5: Use a stereomicroscope to perform particle size detection and color observation on the sample (adjust the brightness within the range of 70-100 according to the field of view, observe the contrast and color of the mixed powder sample), and record D. 90 The values are 108.37 μm, 101.33 μm, 110.43 μm, and 115.89 μm, respectively, with a calculated relative standard deviation of 5.52%.
[0094] Step S6: Based on steps S4 and S5, the relative standard deviation of the weights of the four samples is within 5%, D 90 If the relative standard deviation exceeds 2.5%, the powder mixture is considered unevenly mixed.
[0095] The results of the evaluation of each embodiment and comparative example are summarized in Table 1.
[0096] Table 1 In this context, “√” represents “meets the standard or”, “×” represents “does not meet the standard or”, and “——” represents that the item was not tested.
[0097] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for testing the uniformity of aluminum-based composite powder, characterized in that, Includes the following steps: S1: Samples were taken from four different locations in the aluminum-based composite powder, and the sample volumes of the four samples were the same. S2: Weigh the four samples taken and calculate the relative standard deviation of the weight; S3: Perform particle size analysis and color observation on the four samples taken, and record the results. 90 And calculate the relative standard deviation of particle size; S4: Uniformity judgment: If the relative standard deviation of the weight of the four samples exceeds 5%, then step S3 is not required, and the aluminum-based composite powder is directly judged to be non-uniform; if the relative standard deviation of the weight of the four samples is within 5%, then step S3 is performed; if the relative standard deviation of the particle size of the four samples is within 2.5% and the color is uniform, the aluminum-based composite powder is judged to be uniform.
2. The method for testing the uniformity of aluminum-based composite material powder as described in claim 1, characterized in that, The four different locations are specifically the east, west, south, and north.
3. The method for testing the uniformity of aluminum-based composite powder as described in claim 1, characterized in that, The sampling is specifically performed using a sampler with a fixed volume.
4. The method for testing the uniformity of aluminum-based composite powder as described in claim 1, characterized in that, The sampling volume is 1 cm³. 3 .
5. The method for testing the uniformity of aluminum-based composite powder as described in claim 1, characterized in that, The particle size detection and color observation were performed using a stereomicroscope.
6. The method for testing the uniformity of aluminum-based composite powder as described in claim 5, characterized in that, When observing color, the brightness of a stereomicroscope should be 70-100.
7. The method for testing the uniformity of aluminum-based composite powder as described in claim 1, characterized in that, The aluminum-based composite powder is composed of aluminum matrix powder and reinforcing particles.
8. The method for testing the uniformity of aluminum-based composite powder as described in claim 7, characterized in that, The reinforcing particles are SiC particles.